To Explore Hotel Service Factors Effect on Increasing Tourist Loyalty-Malaysia Evidence (Preliminary Study) - Nezakati, Hossein (Journal of Education and Vocational Research, 2012)
Tourism industry has become more important in the global economy because it has the fastest growth in recent years. Based on United nation world tourist organization, Malaysia is the 9th country in the world and 3rd country in Asia in attracting tourists with 24.6 million one in 2010. Hotels play important role by providing quality service to customers and enhancing their loyalty. Rapid growth among hotels in tourism industry make hotels to recognize services as an important factor attracting more tourists, hence those are profitable. Therefore this primary study tries to start finding out relationship between important aspects of services such as process, place and personnel in hotels with tourist length of staying and frequency intention to revisit. Other research objectives are to investigate the effect of tourist’s length of stay and frequency intention to revisit on tourist loyalty.